Pioglitazone Enhances Cytosolic Lipolysis, β-oxidation and Autophagy to Ameliorate Hepatic Steatosis - Hsiao, Pi-Jung (Sci Rep, 2017)
Non-alcoholic fatty liver disease closely contributes to the development of obesity and insulin resistance. Even though pioglitazone has been reported to effectively lessen hepatic steatosis in human studies, its molecular mechanism remains unclear. This study is designed to investigate the regulation of cytosolic lipolysis, β-oxidation and autophagy by pioglitazone in a mice model of high fat diet (HFD) and cell model incubated with palmitic acid. Our results revealed hepatic steatosis was apparently induced by HFD and it was significantly reversed by pioglitazone. The serum insulin and hepatic triglyceride content was significantly decreased by co-administered pioglitazone with HFD. Hepatic expression of cytosolic-lipolysis related proteins (ATGL, HSL), β-oxidation (CPT-1A) and autophagy-related proteins (ATG7, LC3, LAL) was significantly enhanced by pioglitazone. Knockdown PPARα/PPARγ in AML12 cells significantly and proportionally reduced the expressions of ATGL, CPT-1A and LC3II, which was induced by pioglitazone. Furthermore, facilitation of the autophagic flux by pioglitazone was obviously blocked by lysosomal inhibitor, leupeptin, to demonstrate accumulation of the LC3II and intracellular lipid in AML12 cells. Our results demonstrated that pioglitazone attenuating the hepatic steatosis may be mediated by enhancing cytosolic lipolysis, β-oxidation and autophagy in a PPARα and PPARγ dependent manner.